Computational insights into the photochemical step of the reaction catalyzed by protochlorophylide oxidoreductase - Silva, Pedro J. (2012)
The light-dependent enzyme protochlorophyllide oxidoreductase (EC:1.3.1.33) catalyzes the conversion of protochlorophyllide (PChlide) into chlorophyllide during chlorophyll synthesis. The reaction has been proposed to proceed through light-induced weakening of the C17–C18 double bond in PChlide, which then facilitates hydride transfer from a NADPH cosubstrate molecule. We have performed DFT and TDDFT computations on the reaction mechanism of this interesting enzyme. The results show that whereas in the ground state the reaction is strongly endergonic and has a very high activation free energy (38 kcal/mol), the first four excited states (corresponding to excitations within the conjugated porphyrin π-system) afford much lower activation free energies (<25 kcal/mol) and spontaneous (or only slightly endergonic) reaction paths. The sharp shape of the potential energy surface along the reaction coordinate in these excited states allows hydrogen tunneling to occur efficiently on the first few excited state surface, lowering the barrier to values closer to experiment, in agreement with recent suggestions.